Corporate crime, the lawmaker's options for corporate criminal laws and Luhmann's concept of "useful illegality" - Schröder, Thomas (International journal of law, crime and justice, 2019)
The article contributes to the current discussion on whether and how to introduce corporate criminal responsibility to Germany. The article focuses on the interrelation between possible designs of a future corporate criminal law and the explanatory model of the "early" Niklas Luhmann (1964) on the existence and functionality of "useful illegality" ("brauchbare Illegalität") in organisations. The author presents the alternatives for penal legislature, discusses the original concept of Luhmann and debates his recent "rediscovery" and popularisation in the context of publicly debated corporate misconduct. The key question is whether, for reasons of efficiency, the law should allow companies leeway for useful deviant behaviour. As a rule, severe violations of state law are neither desirable nor useful. However, the "uselessness" depends on the "accounting period". Rather, the author takes the view that law itself endeavours as far as possible to systematically implement socially beneficial behaviour in the binary code "right-wrong".
Received 15 June 2018; Received in revised form 14 December 2018; Accepted 21 January 2019; Available online 16 February 2019
Gesehen am 25.09.2019